The Plant Life of China Diversity and Distribution - Chapman, Geoffrey P.; Wang, Yin-Zheng (Springer Berlin Heidelberg, 2002)
Chinese plant life is estimated to include up to 30,000 species and extends from the Himalayan snow line across a diversity of habitats to the lush tropical south. It is embraced by a culture going back more than 3000 years, providing plants for medicinal use and some of the most valued horticultural species. Although for many years access to Chinese plants was limited, the present situation provides an opportunity for a new and authoritative assessment of such botanical treasure-houses as Yunnan and Sichuan. The present book provides an overview of the subject and is fully referenced and indexed. It will be of interest to those working in agriculture, alternative medicine, plant conservation, ecology, genetics, horticulture, molecular biology and taxonomy
Keywords: Plant Sciences; Ecology; Agriculture; Forestry; Acupuncture; Pharmacology/Toxicology; Botany; Forests and forestry; Toxicology; Pflanzenökologie; Pflanzen; China